2015
DOI: 10.1021/jf506267r
|View full text |Cite
|
Sign up to set email alerts
|

Probing Conformational Change of Bovine Serum Albumin–Dextran Conjugates under Controlled Dry Heating

Abstract: The time-dependent conformational change of bovine serum album (BSA) during Maillard reaction with dextran under controlled dry heating has been studied by small-angle X-ray scattering, fluorescence spectroscopy, dynamic light scattering, and circular dichroism analysis. Through the research on the radii of gyration (Rg), intrinsic fluorescence, and secondary structure, conjugates with dextran coating were found to inhibit BSA aggregation and preserve the secondary structure of native BSA against long-time hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…The native BSA molecule showed a strong and clear band at 66 kDa, corresponding to the molecular weight of native BSA. In addition, the native BSA also exhibited several smear bands at higher molecular weights ranging from 150 to 300 kDa, which could be due to the impurities or aggregates of BSA monomers during heating process of sample preparation for SDA-PAGE 2628 . Maillard reaction between BSA and dextran had a prominent effect on the molecular weight profile.…”
Section: Resultsmentioning
confidence: 99%
“…The native BSA molecule showed a strong and clear band at 66 kDa, corresponding to the molecular weight of native BSA. In addition, the native BSA also exhibited several smear bands at higher molecular weights ranging from 150 to 300 kDa, which could be due to the impurities or aggregates of BSA monomers during heating process of sample preparation for SDA-PAGE 2628 . Maillard reaction between BSA and dextran had a prominent effect on the molecular weight profile.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors observed that conjugation of proteins and polysaccharides through Maillard reaction can minimize the structural loss of the protein by protein aggregation during dry heat treatment (Spotti, et al, 2014;Y. Sun, Hayakawa, & Izumori, 2004;Xia, et al, 2015). In fact, aggregation and Maillard reaction can happen simultaneously and it was reported previously that BSA aggregation upon dry heating can be reduced in the presence of Dextran since it can prevent extra aggregation of BSA (Xia, et al, 2015).…”
Section: Sds-page Analysismentioning
confidence: 99%
“…The latter could be due to the steric hindrance of the LMP which was already attached to WPI. Upon dry heating of BSA with dextran, it was found that a steady state reaction was obtained due to the hindrance from the dextran attached in the BSA (Xia, et al, 2015).…”
Section: Tnbs Analysismentioning
confidence: 99%
See 2 more Smart Citations